Шпиндельний вузол установки з розпилення порошків металів - Іскович-Лотоцький, Ростислав; Іванчук, Ярослав; Веселовський, Ярослав (КІНПАТРІ ЛТД, 2013)
Designed for installation of metal powders, which allows to obtain powders of refractory metals, small size, regular shape because of the installation used a special cooling system that allows the installation of cool fully. Also developed drives the workpiece and rotational motion, which provide a uniform flow of the process of formation of powders.
Spindle unit setup with the spraying of metal powders